The Effect of Microwave Heating on Permeability of Bamboo - Krisdianto Krisdianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2008)
Bamboos are plants of enormous importance to the rural people in several regions of Asia. In spite of its many excellent properties; bamboo is liable to biological deterioration. Therefore, a preservative treatment is regarded as necessary. Many methods have been developed to increase the durability of bamboo. However, most of the methods take a long time and in most cases the vessels do not take enough liquid to preserve the surrounding fibres and parenchyma. This study is aimed to observe the effect of microwave heating on bamboo permeability. The study evaluates the moisture content reduction, resin uptake and saturation as well as resin distribution.The result shows that microwave heating is able to reduce the moisture content reduction of both round and split bamboo up to 93% in about 3 minutes. The microwave heating increases the resin uptake of microwave treated bamboo up to 3 ~ 5 times. The resin saturation also improves to about 2.5 ~ 3 times (before curing) and about 4 ~ 5 times (after curing). Resin penetrates mostly through radial checks that occur during drying. Microwave heated samples shows more blackened area in ground parenchyma tissue than non-treated samples, which indicates that the resin was distributed more evenly. It is concluded that microwave heating leads to improve of bamboo permeability. It is recommended that further research be carried out to establish a microwave regime for optimal bamboo permeability.